Surgical site infections after stabilization of pelvic ring injuries: a retrospective analysis of risk factors and a meta-analysis of similar studies - Salášek, Martin; Český, Richard; Whitley, Adam; Šídlo, Kryštof; Klézl, Petr; Džupa, Valér (International orthopaedics, 2023)
PURPOSE: Pelvic ring fractures requiring surgical stabilization are severe injuries. Surgical site infections occurring after stabilization of the pelvis are serious complications, requiring complex and multidisciplinary treatment. METHODS: This is a retrospective observational study from a level I trauma centre. One hundred and ninety-two patients who underwent stabilization of closed pelvic ring injuries without signs of pathological fracture were selected for inclusion into the study. After excluding seven patients for having incomplete data, the final study group consisted of 185 patients (117 men and 68 women). Basic epidemiologic data and potential risk factors were recorded and analyzed by Cox regression, Kaplan-Meier curves, and risk ratios in 2 × 2 tables. Categorical variables were compared by Fisher exact tests and chi squared tests. Parametric variables were analyzed with Kruskal-Wallis tests with post hoc Wilcoxon tests. RESULTS: Surgical site infections occurred in 13% of the study group (24 from 185). Eighteen infections occurred in men (15.4%) and six in women (8.8%). There were two significant risk factors in women: age over 50 years (p = 0.0232) and concomitant urogenital trauma (p = 0.0104). The common risk ratio for both these factors was 212.59 (8.78-5148.68), p = 0.0010. No significant risk factors were identified in men despite younger men having a higher incidence of infection (p = 0.1428). CONCLUSION: Overall rate of infectious complications was higher than in the literature, but this might be caused by inclusion of all patients regardless of surgical strategy. Higher age in women and lower age in men were associated with higher infection rates. Concomitant urogenital trauma was a significant risk factor in women.
Keywords: Male; retrospektivní studie; Surgical Wound Infection; Infection; Fracture related infection; Surgical site infection; Fracture Fixation; infekce chirurgické rány; mužské pohlaví; pánevní kosti; lidé; ženské pohlaví; Humans; pozorovací studie jako téma; Observational Studies as Topic; Pelvic ring; Pelvic Bones; Retrospective Studies; Female; fraktury kostí; Risk factor analysis; lidé středního věku; Fractures, Bone; fixace fraktury; Stabilization; Middle Aged